Unveiling the hidden power: How ESG enhanced Indonesian companies' financial flexibility - Ayudya Shinta Yunica; Rofikoh Rokhim (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2023)
Purpose – The company’s investors and lenders increasingly see that ESG is an important aspect to implement and disclose that can determine their investment or lending decision. This decision can impact the firm's capital inflow and financing capability, which can affect the company's financial flexibility. This study aims to show the effect of ESG on financial flexibility and the mediating role of financial constraints. Design/methodology/approach – This study used companies listed on the Indonesia Stock Exchange from 2015 to 2021 as a sample. The final sample included 233 unbalanced panel data points from 48 listed firms. Path analysis and Sobel test are used to test the mediating role of financial constraint. Findings – The results revealed a notable positive influence of ESG performance on financial flexibility. However, both the path analysis and Sobel test findings indicated that financing constraints were unsuccessful in mediating the relationship between a company's ESG performance and financial flexibility, as the direct effect remained stronger. Research limitations/implications – This study only use enterprises from Indonesia as samples. Secondly, this study applied conventional methodologies commonly used in the existing literature to quantify variables. Third, this study relied on Refinitive ESG rating data and did not compare the ESG ratings from multiple institutions. Practical implications – This research's findings prove to company management that adopting ESG practices in Indonesia can positively influence cash flow and financial flexibility. As a result, it incentivizes companies to be more open to voluntarily disclosing ESG-related information. Originality/value – Little research has discussed whether ESG affects financial constraints and financial flexibility in Indonesia. This study also studies the differences in the effect of ESG performance on financial flexibility directly and indirectly through financial constraint as a mediator, which has not been covered in previous studies.